Expression of eosinophil in peripheral blood of patients with COVID‐19 and its clinical significance. Issue 1 (29th October 2020) - Mu, Tong; Yi, Zumu; Wang, Minjin; Wang, Junren; Zhang, Chongwei; Chen, Hong; Bai, Mingxuan; Jiang, Lingyu; Zhang, Yuwei
Abstract: Aims: To investigate the eosinophil cell (EC) expression in peripheral blood of patients infected with severe acute respiratory syndrome coronavirus 2(SARS‐CoV‐2) and its clinical significance of diagnosis and prognosis. Methods: 95 patients, whose nucleic acid test of SARS‐CoV‐2 was positive to make a definite diagnosis of COVID‐19, were selected as the study group. They were admitted at the Chengdu Public Health Clinical Medical Center from January 21 to March 2, 2020. Another 95 healthy subjects and 95 non‐infectious fever patients during the same period were selected as the control group. The BC‐6900 blood cell analyzer was used to continuously observe and detect ECs in 95 patients with COVID‐19 and the control group. The differences in expression levels of ECs in peripheral blood were analyzed. Results: ECs were significantly decreased in 95 (75.8%) COVID‐19 patients ( P  < .01). The absolute EC count IQR was 0.01 × 10⁹/L (0 × 10⁹/L − 0.04 × 10⁹/L), and the EC percentage IQR was 0.3% (0.1% − 0.8%). As the patients' condition improved, the ECs returned to normal, but for those without improvement, ECs continued to decline. Conclusions: ECs decreased remarkably in patients with COVID‐19, and gradually returned to normal after the improvement of the patients' condition, while EC continued to decrease in patients without improvement. It is suggested that ECs have certain clinical significance in the diagnosis and prognosis of COVID‐19, and may be a useful index in the early warning of acute infectious diseases. Abstract : Continuous observation and detection of the eosinophil cell (EC) in patients with COVID‐19 showed that ECs decreased significantly in this group. When the condition improved, the ECs returned to normal, while the ECs of the patients who did not improve continued to decline. It is suggested that ECs have clinical significance in the diagnosis and prognosis of covid‐19, and may be a useful index in the early warning of acute infectious diseases. In addition, the decrease of ECs in three kinds of diseases caused by coronavirus, COVID‐19, Middle East respiratory syndrome and severe acute respiratory syndrome, suggests that coronavirus may damage the immune function of human body and cause immune damage syndrome by attacking the cells in bone marrow.